2020
DOI: 10.1016/j.euros.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Clinical and Academic Urological Practice: A Survey from European Association of Urology Section of Uro-technology

Abstract: Background The unexpected coronavirus disease 2019 (COVID-19) pandemic has spread worldwide rapidly, developing into a global health crisis. At the same time, it has seriously impacted the daily activities in all the fields of urology. Objective To better understand the impact of the COVID-19 pandemic on clinical, academic, and scientific activities as well as on the quality of life of urologists from the main centers in Europe. Design, setting, and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 18 publications
1
27
0
6
Order By: Relevance
“…Recent publications from Poland and Denmark have reported a 30% decrease in the number of referrals for all cancers during the first wave of the pandemic, which is in line with our observations [18,19]. A reduction of urological services has been reported [20][21][22]. For example, a survey of European countries showed that clinical activities were affected in 54% of centres, and that 85% of elective surgeries were cancelled [20].…”
Section: Radical Prostatectomiessupporting
confidence: 90%
See 1 more Smart Citation
“…Recent publications from Poland and Denmark have reported a 30% decrease in the number of referrals for all cancers during the first wave of the pandemic, which is in line with our observations [18,19]. A reduction of urological services has been reported [20][21][22]. For example, a survey of European countries showed that clinical activities were affected in 54% of centres, and that 85% of elective surgeries were cancelled [20].…”
Section: Radical Prostatectomiessupporting
confidence: 90%
“…A reduction of urological services has been reported [20][21][22]. For example, a survey of European countries showed that clinical activities were affected in 54% of centres, and that 85% of elective surgeries were cancelled [20]. Similarly, an international survey reported that 40% of referrals, 80% of biopsies and 70% of radical prostatectomies were postponed [23].…”
Section: Radical Prostatectomiesmentioning
confidence: 99%
“…Sie wurden in Deutschland zu keinem Zeitpunkt der ersten Welle völlig ausgeschöpft. Dies war in unseren europäischen Nachbarländern nicht der Fall [2,3,9,[11][12][13].…”
Section: Reaktionsmuster Der Regierungen In Europa Auf Die Erste Coviunclassified
“…Indeed, this pandemic has resulted in a 20% decrease in urology referrals in the United States [5]. Furthermore, 93% of respondents in a previous study claimed that it affected their clinical practice of urology, with other reports claiming that the pandemic has severely decreased the quality of academic activities and residency training worldwide [6][7][8].…”
Section: Introductionmentioning
confidence: 99%